2004
DOI: 10.1677/joe.0.1820241
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the concentration gradient of prostaglandin H synthase 2 mRNA throughout the pregnant baboon uterus

Abstract: The present study was designed to determine the effect of the spatial gradient from the cervix to the uterine fundus on the control of local prostaglandin H synthase (PGHS) 2 mRNA expression. We performed total cesarean hysterectomies during the last trimester in 12 pregnant baboons, 7 not in labor and 5 in labor, and examined PGHS2 mRNA expression throughout the uterus. PGHS2 mRNA abundance was quantified by in situ hybridization and northern blot analysis in the uterine fundus, lower uterine segment and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Therefore, COX2 is the focal point of our present study. We have recently demonstrated that cervical glandular epithelial cells are the major cell type containing COX2 mRNA and protein in pregnant baboon and sheep (Wu et al 2004b(Wu et al , 2005a. Our data suggest that the cervix is not only the target of prostaglandins but also a site for producing prostaglandins.…”
Section: Introductionmentioning
confidence: 56%
“…Therefore, COX2 is the focal point of our present study. We have recently demonstrated that cervical glandular epithelial cells are the major cell type containing COX2 mRNA and protein in pregnant baboon and sheep (Wu et al 2004b(Wu et al , 2005a. Our data suggest that the cervix is not only the target of prostaglandins but also a site for producing prostaglandins.…”
Section: Introductionmentioning
confidence: 56%
“…COX1 is constitutively expressed in most tissues, and COX2 is an inducible enzyme that responds to inflammatory cytokines and growth factors and is increased in intrauterine tissues during premature and spontaneous term labor [12,13]. We have recently demonstrated that cervical glandular epithelial cells are the major cell type containing COX2 mRNA and protein in pregnant baboon, which peaks near term [14]. Our data suggest that the cervix is not only the target of PGs but also a site for producing PGs.…”
Section: Introductionmentioning
confidence: 70%
“…Samples of polyadenylated RNA (2 g) were separated by electrophoresis on a 1.4% (wt/vol) agarose-0.66 M formaldehyde gel and transferred onto a nylon membrane (NEN Life Science) and then subjected to Northern blot analysis for COX2, PTGER2, PTGER4, and ESR1 mRNAs as described previously [13,14,20,22]. Cyclophilin mRNA was used to control RNA loading.…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations